Preparation of Super Absorbent and Highly Active Fish Collagen Sponge and its Hemostatic Effect in vivo and in vitro - Wang, Lei; Li, Wenjun; Qu, Yan; Wang, Kai; Lv, Kangning; He, Xiaoli; Qin, Song (Frontiers in Bioengineering and Biotechnology, 2022)
Effective control of acute wound hemorrhage caused by battlefields, car accidents, natural disasters can highly improve patients’ survival rates. Nevertheless, hemostatic materials on present market have various defects and limitations. This study utilizes tilapia to extract macromolecular type I collagen to prepare a new hemostatic sponge for controlling acute wound bleeding. The extracted fish collagen has high purity, uniform molecular size and high hydroxyproline content. The peptide chain structure and natural high-level structure are intactly preserved. The infrared absorption spectrum showcases that it preserves all the characteristic absorption bands of type I collagen. The developed hemostatic sponge has a uniform honeycomb-shaped porous structure and high water absorption capacity. The biological safety test illustrates that the sponge cell has good compatibility and it will not trigger any inflammatory reaction or immune rejection reactions in the body. The sponge cell could be degraded gradually and completely, which has good biocompatibility and degradation performance. The result of in vitro experiments shows that certain groups or structures in fish collagen molecules can combine specific sites on the surface of blood cells and platelets, which can quickly activate platelets and coagulation system to obtain better coagulation function. The result of In vivo experiments further shows that the fish collagen sponge has fast coagulation speed and low bleeding during the hemostasis process of rabbit ear arteries and rat liver wounds, which proves that it has excellent coagulation performance.